Hiroshima - Wilmshurst, Paul (United Kingdom : BBC, 2005)
A film telling the story of the atomic bomb and its impact on the people of Hiroshima. The film mixes oral history, archival footage, CGI and full-scale reconstruction to illustrate and understand an incomprehensible part of human history.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films